The risk and prevention of sudden death in patients with heart failure with reduced ejection fraction. (March 2020) - Davis, Jason; Sapp, John
Abstract : Purpose of review: Patients with heart failure are at increased risk of sudden cardiac death. The methods to predict patients at high risk of sudden cardiac death in heart failure are neither sensitive nor specific; both overestimating risk in those with ejection fractions less than 35% and not identifying those at risk with ejection fractions greater than 35%. Recent findings: The absolute risk of sudden cardiac death in patients with heart failure have decreased over the past 20 years. New novel tools are being developed and tested to identify those at higher risk of sudden cardiac death. Reduction in the risk of sudden cardiac death has been achieved with the use of beta-blockers, spironolactone, sacubitril–valsartan, cardiac resynchronization and implantable cardioverter defibrillators. Summary: The use of contemporary treatments for patients with heart failure can reduce the risk of sudden cardiac death, but research is required to identify those at highest risk.